Acculturation, vitality, and bilingual healthcare - Bourhis, Richard Y.; Montreuil, Annie (The Oxford handbook of acculturation and health, 2017)
Chapter: 4

Health and healthcare utilization of Francophones in Manitoba - Chartier, Mariette; Finlayson, Gregory. S.; Prior, Heather. J.; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, 2012)

La santé et l'utilisation des services de santé des francophones du Manitoba - Chartier, Mariette; Finlayson, Gregory. S.; Prior, Heather. J.; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, 2012)

Agir ! Pour ma santé : une intervention harmonisant Services médicaux et diagnostiques et services communautaires pour les Franco-Manitobains souffrant de dépression - de Moissac, Danielle; Bohémier, Moniqu; Herdman, Chelsea; Roch-Gagné, Margaux; Paillé, Julie; Johnston, Christine; Arpin-Molinski, Michelle; Dupuis, Georgette; Saint-Hilaire, Mélanie; Prairie, Liliane (Reflets, 2012)

Insight into Post-Pandemic Needs in Healthcare and Well-Being Among Francophone Families in the Canadian Prairies - Keough, Catelyn; Turgeon, Marianne; Proulx-Cullen, Elyse; Leis, Anne; De Moissac, Danielle; Marchak, Kristan; Gnidehou, Sedami (International Journal of Environmental Research and Public Health, 2026)
Francophone populations outside Quebec were disproportionately affected by the COVID-19 crisis. Despite French being one of Canada’s official languages, access to information and services in French remains limited. This study examined Francophone families’ (FF) post-pandemic health and well-being needs (PPHW) in the Canadian Prairie provinces. An online survey assessed PPHW needs among 319 FF in Alberta (AB), Saskatchewan (SK), and Manitoba (MB). Respondents ranked PPHW needs from a predefined list; logistic regression analyzed socio-demographic influences. Divided into AB/SK and MB cohorts, sociodemographic profiles were statistically distinct for many variables, but with similarities found in gender of respondents (women: 73% in AB/SK, 79% in MB), marital status (married: 81% in AB/SK, 88% in MB), area of residence (urban: 86% in AB/SK, 81% in MB), and number of children (2 children: 49% in AB/SK, 41% in MB). Three high-priority needs were shared across provinces: (1) access to recreational, athletic, and artistic activities in French for children (variations by child gender); (2) access to French healthcare professionals (variations by education level and language difference); and (3) social activities in French for families. AB/SK respondents prioritized mental health services in French for adults and youth. MB families prioritized belonging to a Francophone community (variations by gender of children) and education services in French (variations by age of children). Understanding these common and province-specific priorities can inform policy and service planning.

L’influence de l’identité linguistique et de l’âge sur la représentation sociale des services de santé mentale chez les personnes dites dépressives - Lévesque, Maude; Negura, Lilian; Moreau, Nicolas; Laflamme-Lagoke, M. (Minorités linguistiques et société, 2018)
Cet article étudie la représentation sociale des services de santé mentale chez les personnes dites dépressives en contexte francophone minoritaire au Canada. Des entrevues semi-dirigées ont été réalisées auprès de 44 personnes s’identifiant comme francophones et anglophones. Ces dernières proviennent de Moncton, Ottawa, Sudbury et Winnipeg et ont fait l’expérience d’un épisode dépressif. L’analyse lexicographique complétée par l’analyse intégrée de contenu a fait ressortir trois grands schèmes sociocognitifs de la représentation sociale des services, qui agissent sur l’acceptabilité sociale des services de santé mentale chez les personnes francophones vivant en situation minoritaire : 1) la nature impersonnelle des compétences expertes des professionnels de la santé, 2) la facette médicale de l’identité dépressive et 3) la perte perçue du contrôle dans le contexte de soins. L’acceptabilité sociale des services de santé mentale est discutée également en fonction de la configuration de la représentation sociale des services selon l’âge. Mots-clés : minorité linguistique, francophones, santé mentale, services, dépression, représentation sociale

Strategies to improve French language health and social service continuity for seniors in Ontario and Manitoba - Savard, Jacinthe; Savard, Sébastien; de Moissac, Danielle; Giasson, Florette; Kubina, Lucy-Ann (Linguistic Minorities and Society, 2021)
Access to health and social services in one’s official language of choice is an important component of quality and safety of care for seniors. Access can be fragmented, even in the context of legislation guaranteeing the right to receive such services, and in areas with a higher proportion of bilingual providers. Using a community-based participatory approach, we identified mechanisms promoting or impeding the clinical integration of health and social French language services intended for seniors living in two Canadian Francophone minority communities. Thirteen recommendations highlight the possibility for new initiatives to promote a continuum of French language health and social services in a minority context, involving collaboration among a variety of actors at all levels of our analytical framework: service trajectory (providers); francophone communities; organizational; political and regulatory; and symbolic (values) structures. Keywords: seniors, linguistic minorities, service integration, health and social services, continuity of care